If we could turn back time: Imagining time-variable, competency-based medical education in the context of COVID-19. (3rd July 2021) - Caretta-Weyer, Holly A.; Chan, Teresa; Bigham, Blair L.; Kinnear, Benjamin; Huwendiek, Sören; Schumacher, Daniel J.; ,
Abstract: The COVID-19 pandemic has exposed a paradox in historical models of medical education: organizations responsible for applying consistent standards for progression have needed to adapt to training environments marked by inconsistency and change. Although some institutions have maintained their traditional requirements, others have accelerated their programs to rush nearly graduated trainees to the front lines. One interpretation of the unplanned shortening of the duration of training programs during a crisis is that standards have been lowered. But it is also possible that these trainees were examined according to the same standards as usual and were judged to have already met them. This paper discusses the impacts of the COVID-19 pandemic on the current workforce, provides an analysis of how competency-based medical education (CBME) in the context of the pandemic might have mitigated wide-scale disruption, and identifies structural barriers to achieving an ideal state. The paper further calls upon universities, health centres, governments, certifying bodies, regulatory authorities, and health care professionals to work collectively on a truly time-variable model of CBME. The pandemic has made clear that time variability in medical education already exists and should be adopted widely and formally. If our systems today had used a framework of outcome competencies, sequenced progression, tailored learning, focused instruction, and programmatic assessment, we may have been even more nimble in changing our systems to care for our patients with COVID-19.